Android-Based M-Learning Application to Improve Pancasila Education Learning Outcomes - Ilmi, Novalisna Nurul; Aeni, Kurotul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The lack of learning media in learning activities impacts low learning outcomes. This research aims to develop an Android-based m-learning application to improve learning outcomes in Pancasila class education. This type of research is development research (Research and Development/R&D). The model used in developing the product is ADDIE. The subjects of this research are learning materials experts and learning media experts. The test subjects were 39 class V students. The sampling technique used was purposive sampling. The methods used to collect data are tests and non-tests (observation, interviews, questionnaires, questionnaires and documentation). Data collection instruments use questionnaires and test questions. The techniques used to analyze data are qualitative descriptive analysis and quantitative and inferential statistics. The research results were that material and media experts rated the final product as 'very worthy' with an impressive average score of 90%. The results of the effectiveness test show that there are differences in student learning outcomes after implementing the Android-based m-learning application. The N-gain calculation obtained a value of 0.5683 with